2011
DOI: 10.1016/j.mce.2010.12.019
|View full text |Cite
|
Sign up to set email alerts
|

GATA4 regulates Sertoli cell function and fertility in adult male mice☆

Abstract: Transcription factor GATA4 is expressed in Sertoli and Leydig cells and is required for proper development of the murine fetal testis. The role of GATA4 in adult testicular function, however, has remained unclear due to prenatal lethality of mice harboring homozygous mutations in Gata4. To characterize the function of GATA4 in the adult testis, we generated mice in which Gata4 was conditionally deleted in Sertoli cells using Cre-LoxP recombination with Amhr2-Cre. Conditional knockout (cKO) mice developed age-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 77 publications
5
83
1
Order By: Relevance
“…Abnormal seminiferous tubular architecture accompanied with irregularly arranged germ cells, vacuoles, and giant cells in the gonadspecific Nr5a1 KO testes became apparent by P14. Intratubular vacuoles have been reported in other KO mice, in which spermatogenesis was impaired and is associated with Sertoli cell damage (Hellsten et al 2002, Kyrönlahti et al 2011. In fact, we observed that many of the vacuoles detected in the KO mice were accompanied by a nucleus positive for the Sertoli cell marker SOX9 (Fig.…”
Section: (A B C D E F G and H) Representative Images Of Immunoesupporting
confidence: 67%
“…Abnormal seminiferous tubular architecture accompanied with irregularly arranged germ cells, vacuoles, and giant cells in the gonadspecific Nr5a1 KO testes became apparent by P14. Intratubular vacuoles have been reported in other KO mice, in which spermatogenesis was impaired and is associated with Sertoli cell damage (Hellsten et al 2002, Kyrönlahti et al 2011. In fact, we observed that many of the vacuoles detected in the KO mice were accompanied by a nucleus positive for the Sertoli cell marker SOX9 (Fig.…”
Section: (A B C D E F G and H) Representative Images Of Immunoesupporting
confidence: 67%
“…Similar defects also occur in mouse testes lacking the fibronectin domain-containing protein FNDC3A (originally described as the symplastic spermatid "sys" mutation [37,54]), the glycosylated cell adhesion molecule Cadm1 (55,56), the multifunctional glycoprotein Basigin (57), and the glycosyltransferase Mgat1 (58). Strikingly, loss of Sertoli cell-restricted proteins (Cib1, Inpp5b, and Gata4) also results in apoptosis of germ cells and MNC formation (59)(60)(61), further highlighting the importance of germ-Sertoli cell interaction. Notably, cKO MNCs displayed apoptotic features, including chromatin condensation and cell shrinkage, but were TUNEL negative, suggesting that apoptosis of spermatocytes and spermatids in cKO testes may occur via distinct mechanisms.…”
Section: Discussionmentioning
confidence: 81%
“…Consistent with this expression pattern, different genetic mouse models have begun to illuminate the complex and essential roles played by this transcription factor in the very first steps of gonadal development and later, for male and female fertility (Kyrönlahti et al 2011a,b, Manuylov et al 2011, Bennett et al 2012, Efimenko et al 2013, Hu et al 2013, Tevosian 2014. While these studies clearly established the essential nature of GATA4 in reproduction, understanding how GATA4 accomplishes these tasks, i.e., identifying its target genes and thus its mechanism of action, remains incomplete.…”
Section: Discussionmentioning
confidence: 99%